Intellectual and political trends and their impact on modern poetry -: Blend Haidari - Anmozja - محسن بشرى حنون; جواد انوار سعيد (Al-Adab Journal, 2019)
In the name of God the Creator and the great prayer upon the most honorable creature, whom God sent him to guide the creation of Sydney and the Prophet Muhammad peace be upon him and the family of his home and his family close. After: The poem Free became a poem many intellectual implications and that the culture of the poet became inclusive culture, you need to critic holistic to fathom the depths of a literary work, provided by poet modernist and it includes the shift and the ambiguity and the dimensions of semantic vary depending on the culture and poetic talent and everything organized under the banner of creativity. The readerof thepoemTrocheefeelthat most of thepoets ofmodernitystems fromconcernasthe worldwideobsessiondefeat at thepersonal andthe publicwith aprofoundhopefor a newadvancementof this nationupto its pastpresentdeterioratingbrightfuturedirection ofthe founding ofthe Shining. When standing researcher in front of the circumstances experienced by Iraq in the forties of the last century, see how the harsh conditions in the political, social, intellectual and economic sphere, and had these circumstances returns negative poets in that period we mean since the end of the forties, where they suffer from the forces of oppression, injustice and horror the country and the forces of evil that Tgk govern the world and although the Iraqi poets have expressed those conditions in most of the poems, but they at the same time were optimistic and dream of the sun of freedom and revolution against tyranny and perhaps Sayyab was more these poets expression mediated by the legendary symbols of the political and intellectual barrenness which experienced by Iraq It remains creativity aware individually and collectively shaped by the acculturation cultural and intellectual with different walks, it does not mean specifically that the stripes be the last, in spite of the importance of this past and its role in the formation of many new creative works. And culture that constitutes the vision of the poet of the world, is the spirit that is common in self-test, the magic to move from the private to the public, Vtdvi the vitality and sustainability. Theculture ofthe poetcannot bedefineda culturalelementresults, but intercoursefor manyexperiences, and that’s whatwe’ll findevident in thehairBlendHaidarias itportraysusmodern humansbrokenlostwillsufferanxietyin light ofthose fakemonotonouscivilization, thus expressedalienationand humanitarianconcernofdeathand unityand isolation